Influence of Supporting Electrolyte on Hydroxide Exchange Membrane Water Electrolysis Performance: Catholyte. Issue 2 (1st February 2022) - Kiessling, Aleksandr; Fornaciari, Julie C.; Anderson, Grace; Peng, Xiong; Gerstmayr, Andreas; Gerhardt, Michael; McKinney, Samuel; Serov, Alexey; Weber, Adam Z.; Kim, Yu Seung; Zulevi, Barr; Danilovic, Nemanja
Abstract : Alkaline or hydroxide exchange membrane water electrolysis (HEMWE) is a promising technology for green hydrogen production using platinum group metal-free catalysts and stainless steel, an advantage of alkaline water electrolysis (AWE), and a gas-impermeable membrane, a parallel to proton exchange membrane electrolysis (PEMWE). However, the HEMWE requires supporting electrolytes and there is minimal understanding of their role on the respective reactions. Without SELs, HEMWE performance and durability are worse than PEMWE systems. Herein, consistently feeding potassium hydroxide anolyte, we systematically study the effects of catholyte SELs in HEMWEs including dry vs. wet operation, cation effects, anion effects, and cation/OH ratios on cell potential and stability. We report that (i) hydration of the cathode improves high current density operation by preventing dehydration of the hydroxide exchange membrane (HEM), (ii) there was no correlation between cation type and cell potential, (iii) cell potential and high frequency resistance did not correlate with SEL conductivity, (iv) cathodic carbonate SEL had a significant negative effect on cell performance, (v) increased cation/OH ratio also caused increased cell potentials. Overall, this study concludes that feeding water or potassium hydroxide solution is desirable to improve the AEMWE performance.